Aetiology of lower respiratory tract infection in adults in primary care: a prospective study in 11 European countries. (November 2018) - Ieven, M.; Coenen, S.; Loens, K.; Lammens, C.; Coenjaerts, F.; Vanderstraeten, A.; Henriques-Normark, B.; Crook, D.; Huygen, K.; Butler, C.C.; Verheij, T.J.M.; Little, P.; et al.
Abstract: Objectives: To describe the role of bacteria (including bacterial resistance), viruses (including those recently described) and mixed bacterial–viral infections in adults presenting to primary care with lower respiratory tract infection (LRTI). Methods: In all, 3104 adults with LRTI were enrolled, of whom 141 (4.5%) had community-acquired pneumonia (CAP), and 2985 matched controls in a prospective study in 16 primary care networks in Europe, and followed patients up at 28–35 days. We detected Streptococcus pneumoniae and Haemophilus influenzae and assessed susceptibility, atypical bacteria and viruses. Results: A potential pathogen was detected in 1844 (59%) (in 350 (11%) bacterial pathogens only, in 1190 (38%) viral pathogens only, and in 304 (10%) both bacterial and viral pathogens). The most common bacterial pathogens isolated were S. pneumoniae (5.5% overall, 9.2% in CAP patients) and H. influenzae (5.4% overall, 14.2% in CAP patients). Less than 1% of S. pneumoniae were highly resistant to penicillin and 12.6% of H. influenzae were β-lactamase positive. The most common viral pathogens detected were human rhinovirus (20.1%), influenza viruses (9.9%), and human coronavirus (7.4%). Influenza virus, human parainfluenza viruses and human respiratory syncytial virus as well as human rhinovirus, human coronavirus and human metapneumovirus were detected significantly more frequently in LRTI patients than in controls. Conclusions: A bacterial pathogen is identified in approximately one in five adult patients with LRTI in primary care, and a viral pathogen in just under half, with mixed infections in one in ten. Penicillin-resistant pneumococci and β-lactamase-producing H. influenzae are uncommon. These new findings support a restrictive approach to antibiotic prescribing for LRTI and the use of first-line, narrow-spectrum agents in primary care.